Aktivisme, Budaya Populer, Pemuda, dan Media: Analisis Bingkai dan Paradigma Protes terhadap Three Finger Salute dalam Berita Reuters - Antara, I Putu Juni; Irawanto, Budi (Jurnal Studi Pemuda, 2023)
This study investigates the framing and presences of the protest paradigm in Reuters' coverage of activism events in Southeast Asia involving The Hunger Games' Three Finger Salute. In recent years, several protests in the region have adopted this salute as a means of expressing dissent against their respective governments. These diverse activisms not only attract media attention as political events but also signify interconnected political phenomena through a gesture inspired by popular narratives such The Hunger Games. Reuters, an international news agency, has shown a heightened interest in this phenomenon compared to other news agencies that focusing solely on political activities. While it is common for news reports to embody the protest paradigm when covering activism, Reuters' coverage specific focus on events involving the Three Finger Salute sets it apart. The protest paradigm highlights the media's tendency to depict social protests with a negative sentiment. Through text and framing analysis, this research delves into how Reuters selectively emphasizes certain aspects of these fan activisms. The findings reveal that Reuters framed the coverage of fan activisms around authoritarian government, youth and student, and royalist. Reuters also has negative sentiment and continues to perpetuate the protest paradigm.